Investigation of Causality Analysis between Economic Growth and CO2 Emissions: The Case of BRICS – T Countries - Erdoğan, Seyfettin; Yıldırım, Durmuş Çağrı; Gedikli, Ayfer (International Journal of Energy Economics and Policy, 2019)
The most significant cost of increase in economic growth is an increase in energy consumption and carbon emissions as well. Energy consumption triggers carbon dioxide emissions, which is the main cause of environmental pollution. In recent years, struggling with climate changes, global warming and carbon dioxide emissions based environmental problems became critical issues. In doing so, this study investigates the relationship between carbon emissions and economic growth for BRICS-T countries for the period of 1992-2016. We apply Pedroni and, Westerlund and Edgerton panel cointegration approaches for examining cointegration between the variabes. The FMOLS approach is applied for testing long-term relationship between economic growth and carbon emissions. The empirical results indicate that a 1% increase in economic growth increases carbon emissions by 0.79% but 1% increase in carbon emissions leads economic growth by 0.5%. The causality analysis reveals the presence of bidirectional relationship between carbon emissions and economic growth. Keywords: Carbon Emissions, Economic Growth, BRICS-T Countries JEL Classifications: P52, O10 DOI: https://doi.org/10.32479/ijeep.8546